Innovating Sharia Fintech : Harnessing Sukuk to Drive Sustainable Infrastructure Development in Emerging Economies - Septantri Shinta Wulandari (International Forum of Researchers and Lecturers, 2025)
This paper explores the potential of integrating Sharia-compliant financial technology (fintech) innovations with sukuk issuance to drive sustainable infrastructure development in emerging economies. With the rise of digital transformation and the increasing focus on sustainable development, the Islamic financial system provides a unique opportunity to reconcile financial innovation with ethical principles. The study highlights how Sharia fintech platforms, such as crowdfunding and blockchain, can enhance the efficiency, transparency, and accessibility of sukuk as a financial instrument. At the same time, sukuk addresses the significant financing gap in infrastructure development while adhering to Islamic principles, such as avoiding riba (interest), gharar (uncertainty), and maysir (speculation). Through a comprehensive literature review and empirical analysis, this research identifies the gaps in existing approaches to financing sustainable infrastructure in emerging economies and proposes a novel integration framework. Findings suggest that the convergence of Sharia fintech and sukuk can facilitate financial inclusion, attract a broader investor base, and accelerate infrastructure financing. Furthermore, this integration supports the achievement of the Sustainable Development Goals (SDGs) by ensuring that financial tools align with social justice and environmental stewardship. This study contributes to the growing body of knowledge on Islamic finance by providing actionable insights for policymakers, financial institutions, and fintech developers. It emphasizes the importance of regulatory frameworks and cross-sector collaboration to unlock the full potential of Sharia-complian